Effect of root growth on slope hydrology and stability during early plant establishment - Kamchoom, Viroon; Jotisankasa, A. (My University, 2020)
The roots developed during early plant establishment could affect soil hydraulic properties, including soil water retention curve (SWRC) and hydraulic conductivity function (HCF). It remains unclear whether the changes in SWRC and HCF due to root growth are significant to slope stabilisation. This study aims to investigate effect of root growth on slope hydrology and stability during early plant establishment. Finite-element seepage-stability models of 45-degree clayey sand slopes subjected to intense rainfall were developed, with due consideration of coupled hydro-mechanical reinforcement and root-induced changes soil hydraulic properties. The results suggested that root growth increase infiltration rate by almost twice and resulted in significant loss of retained suction. Considering changes of SWRC and HCF influenced by fine roots can reduce slope stability by up to 22%.
Keywords: Grass; Hydraulic conductivity; Numerical modelling; Slope stability; Soil water retention curve; Suction